Aluminium Metal Matrix Composite with Zirconium diboride Reinforcement: A Review. (2018) - Dinesh Kumar, S.; Ravichandran, M.; Meignanamoorthy, M.
Abstract: Aluminium metal matrix composites have the abilities of sustaining the present demands of advanced engineering applications. The physical and mechanical properties that can be acquired with aluminium metal matrix has developing demand in aircraft, automotive and other industries owing to its light weight, high strength to weight ratio, corrosion resistance and workability. More in recent times, particulate reinforced MMCs have concerned significant attention are preferable due to their low cost, constant properties and their skill to be like monolithic materials and characteristic isotropic properties. The potential of these materials is mostly reliant on on choosing the correct combination of reinforcing materials since most of the processing parameters are related with the reinforcing particulates. This article made an effort to review the reinforcing material ZrB2 used in the synthesis of aluminium metal matrix composite and the way it effects the mechanical, corrosion and wear performance of the materials.